Heat dissipation composite material and preparation method and application thereof
By designing a multi-layer structure of adhesive layer, insulating and breathable layer, thermal conductive layer and thermal diffusion layer, the problem of single function of traditional heat dissipation materials is solved, and the effects of efficient thermal conductivity, good insulation and breathability, and close adhesion to heat-generating electronic devices are achieved. It is suitable for heat dissipation of high-power density electronic equipment.
Patent Information
- Application Number
- CN202510801705.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-16
- Publication Date
- 2025-10-03
AI Technical Summary
Traditional heat dissipation materials have a single function and cannot simultaneously meet the requirements of efficient thermal conductivity, good insulation and breathability, and tight adhesion to heat-generating electronic devices.
The structural design adopts an adhesive layer, an insulating and breathable layer, a thermally conductive layer and a thermally conductive diffusion layer arranged in sequence from bottom to top. The adhesive layer is made by a mixed reaction of a polymer matrix material, a composite filler and a molecular bridging agent. The insulating and breathable layer is a porous insulating material. The thermally conductive layer is a graphene film. The thermally conductive diffusion layer is prepared from a porous matrix composite thermally conductive nanoparticles. Stable bonding of each layer is achieved through gradient heating and lamination technology.
It achieves a firm and stable bond between the heat dissipation composite material and the heat-generating electronic devices, significantly improving the heat dissipation efficiency and insulation permeability, and can meet the heat dissipation needs of high-power density electronic equipment.
Smart Images

Figure CN120735443A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of heat dissipation of electronic devices, and in particular to a heat dissipation composite material and a preparation method and application thereof. Background Art
[0002] With the rapid development of electronic technology, the performance of electronic equipment has been continuously improved, resulting in a sharp increase in heat generation. Heat dissipation has become a key factor restricting its performance.
[0003] Currently, a wide variety of heat dissipation materials are widely used. Different types of heat dissipation materials have different properties. Among them, metal materials have good thermal conductivity, especially some metal materials such as copper, aluminum, and silver, which have particularly good thermal conductivity. Graphene film, currently a hot topic of research, has the advantages of thin thickness and high thermal conductivity. However, when the graphene film is combined with an adhesive layer for application, there is a significant interfacial thermal resistance between the traditional graphene film and the adhesive layer, and the graphene layer is prone to interlayer delamination due to thermal stress. Although the graphene film has a certain degree of folding resistance, the strength between the materials is weak and can be easily torn, resulting in damage or the shedding of surface materials. At the same time, the functions of existing heat dissipation materials are relatively simple, and it is often difficult to simultaneously meet the requirements of efficient thermal conductivity, good insulation and breathability, and close adhesion to heat-generating electronic devices.
[0004] Based on this, there is an urgent need to provide a heat dissipation composite material and a preparation method and application thereof. Summary of the Invention
[0005] The embodiments of the present invention provide a heat dissipation composite material and its preparation method and application, which can solve the problem that traditional heat dissipation materials have a single function and are difficult to simultaneously meet the requirements of efficient thermal conductivity, good insulation and air permeability, and tight adhesion with heat-generating electronic devices.
[0006] In a first aspect, the present invention provides a heat dissipation composite material, comprising an adhesive layer, an insulating and breathable layer, a thermally conductive layer, and a thermally conductive diffusion layer arranged in sequence from bottom to top; wherein the adhesive layer is obtained by a mixed reaction of a polymer matrix material, a composite filler, and a molecular bridging agent, the insulating and breathable layer is a porous insulating material, the thermally conductive layer is a graphene film, and the thermally conductive diffusion layer is prepared from porous matrix composite thermally conductive nanoparticles.
[0007] Preferably, the bonding layer is prepared by adding the composite filler and the molecular bridging agent into the polymer matrix material, stirring and mixing, and performing a curing reaction to obtain the bonding layer.
[0008] More preferably, the curing includes UV pre-curing and thermal curing; wherein, the UV pre-curing time is 30-60s, and the thermal curing temperature is 75-85°C and the time is 1-2h.
[0009] Preferably, the composite filler is composed of boron nitride sheets and silver-coated aluminum core-shell particles, the molecular bridging agent is γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, bis-[3-(triethoxysilyl)propyl]tetrasulfide or isopropyl tris(dioctyl pyrophosphate) titanate, and the polymer matrix material is polydimethylsiloxane.
[0010] More preferably, the boron nitride sheets include boron nitride nanosheets and boron nitride microsheets; wherein the particle size of the boron nitride nanosheets is 50-100 nm, and the particle size of the boron nitride microsheets is 10-20 μm.
[0011] More preferably, the mass ratio of the boron nitride nanosheets to the boron nitride microsheets is (4-8):1.
[0012] Preferably, the mass percentages of the raw materials in the bonding layer are as follows: composite filler 45-70%, molecular bridging agent 1-3%, polymer matrix material 27-56%, and the mass ratio of boron nitride sheets and silver-coated aluminum core-shell particles is (8-12): (1-2).
[0013] Preferably, the porous insulating material is expanded polytetrafluoroethylene, expanded polyethylene or expanded polypropylene.
[0014] Preferably, the porosity of the porous insulating material is greater than 30%, and the pore size is greater than 0.1 μm.
[0015] More preferably, the thermal conductivity of the graphene film is 500-5000 W / m·K, and the thickness is 15-20 μm.
[0016] Preferably, the heat dissipation composite material further comprises two thermally conductive transition layers, wherein the thermally conductive transition layers are respectively located between the adhesive layer and the insulating breathable layer, and between the insulating breathable layer and the thermally conductive layer;
[0017] Preferably, the thermally conductive transition layer is obtained by compounding graphene nanosheets, carbon nanotubes, silicon carbide nanowires and boron nitride nanosheets.
[0018] More preferably, the size of graphene nanosheets is 5-20 nm, the content is 40-60%, the size of boron nitride nanosheets is 5-10 nm, the content is 5-15%, the size of carbon nanotubes is 10-50 μm, the content is 20-30%, and the diameter of silicon carbide nanowires is 50-100 nm, the content is 15-25%.
[0019] Preferably, the preparation method of the thermal conductive transition layer is as follows:
[0020] S1, adding graphene nanosheets and boron nitride nanosheets to N-methylpyrrolidone and mixing them by ultrasonication to obtain a first mixed solution;
[0021] S2, adding silicon carbide nanowires and polydimethylsiloxane to the first mixed solution and stirring to obtain a second mixed solution;
[0022] S3, adding carbon nanotubes to the second mixed liquid, stirring and mixing, and applying a vertical magnetic field and gradient temperature curing in sequence to obtain the thermal conductive transition layer.
[0023] More preferably, in the first mixed solution, the ratio of the sum of the mass of the graphene nanosheets and the boron nitride nanosheets to the mass of N-methylpyrrolidone is 1:(5-20).
[0024] More preferably, the mass ratio of silicon carbide nanowires to polydimethylsiloxane is 1:(1-4).
[0025] Preferably, the intensity of the vertical magnetic field is 1-2t, and the temperature of each stage in the gradient temperature rise curing is 70-90°C, 140-160°C, and 240-260°C, respectively, and the time is 1-2h.
[0026] Preferably, the porous matrix is polyvinylidene fluoride, polysulfone, polyether, polypropylene, polyvinyl chloride, polyethylene, polypropylene or polytetrafluoroethylene.
[0027] More preferably, the thermally conductive nanoparticles are copper powder, carbon nanotubes, graphene, silicon carbide or boron nitride.
[0028] In a second aspect, the present invention provides a method for preparing the heat dissipation composite material according to any one of the first aspects above, the preparation method comprising the following steps:
[0029] (1) placing the insulating breathable layer, thermal transition layer, thermal conductive layer and thermal diffusion layer in sequence, and aligning the layers in a laminator;
[0030] (2) controlling the laminator to heat to a preset temperature and then pressurize, and maintaining the preset temperature and preset pressure to allow each layer to solidify and bond, and obtaining a composite layer after cooling;
[0031] (3) Coating an adhesive formed by mixing a composite filler, a molecular bridge agent and a polymer matrix material on the surface of the insulating breathable layer in the composite layer, and obtaining the heat dissipation composite material after curing.
[0032] Preferably, in step (2), the temperature is increased to a preset temperature by gradient, the preset temperature is 100-150° C., the preset pressure is 20-30 MPa, and the holding time is 30-60 min.
[0033] In a third aspect, the present invention further provides a use of the heat dissipation composite material described in any one of the first aspects in heat dissipation of electronic devices.
[0034] Compared with the prior art, the present invention has at least the following beneficial effects:
[0035] In the present invention, a polymer material with adhesive properties is first used as a matrix material, supplemented with a heat-resistant composite filler, and a bonding layer is prepared by mixing and reacting under the action of a molecular bridging agent. The bonding layer serves as a bridge between the heat dissipation composite material and the heat-generating electronic device. The bonding layer prepared by the above method not only provides a stable mechanical connection, but also effectively reduces the interface thermal resistance, thereby promoting heat transfer from the heat-generating electronic device to the heat dissipation composite material; by further compounding an insulating material with a porous structure on the surface of the bonding layer, it is possible to allow air circulation while maintaining electrical insulation, effectively preventing heat accumulation, and further improving the heat dissipation performance; the thermal conductive composite material on the surface of the insulating layer The layer is composed of graphene film, which serves as the main channel for heat transfer and can quickly conduct heat to the thermal diffusion layer. The porous matrix in the thermal diffusion layer not only increases the heat dissipation surface area through its porous structure and improves the radiation heat dissipation efficiency, but also the filled thermal conductive material further strengthens the heat conduction path, so that the heat can be more evenly dispersed into the surrounding environment; in this way, through the combination and structural design of each layer of material, the synergistic effect of the multi-layer structure is achieved, which not only achieves a firm and stable adhesion between the heat dissipation composite material and the heat-generating electronic device, but also significantly improves the heat dissipation efficiency and insulation permeability of the heat dissipation composite material, which can meet the heat dissipation needs of high-power density electronic equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0037] Figure 1 This is a structural schematic diagram of a heat dissipation composite material provided by Example 1 of the present invention; in the figure, 10 is an adhesive layer, 20 is an insulating and breathable layer, 30 is a thermally conductive transition layer, 40 is a thermally conductive layer, and 50 is a thermally conductive diffusion layer. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0039] like Figure 1 As shown, an embodiment of the present invention provides a heat dissipation composite material, comprising an adhesive layer 10, an insulating and breathable layer 20, a thermally conductive layer 40, and a thermally conductive diffusion layer 50 arranged in sequence from bottom to top; wherein, the adhesive layer 10 is obtained by a mixed reaction of a polymer matrix material, a composite filler, and a molecular bridging agent, the insulating and breathable layer 20 is a porous insulating material, the thermally conductive layer 40 is a graphene film, and the thermally conductive diffusion layer 50 is prepared from porous matrix composite thermally conductive nanoparticles.
[0040] In the embodiment of the present invention, a polymer material with adhesiveness is first used as a matrix material, supplemented with a heat-resistant composite filler, and a bonding layer is prepared by mixing and reacting under the action of a molecular bridging agent. The bonding layer serves as a bridge between the heat dissipation composite material and the heat-generating electronic device. The bonding layer prepared by the above method not only provides a stable mechanical connection, but also effectively reduces the interfacial thermal resistance, thereby promoting heat transfer from the heat-generating electronic device to the heat dissipation composite material; by further compounding an insulating material with a porous structure on the surface of the bonding layer, it is possible to allow air circulation while maintaining electrical insulation, effectively preventing heat accumulation, and further improving the heat dissipation performance; the conductive composite material on the surface of the insulating layer The thermal layer is composed of graphene film, which serves as the main channel for heat transfer and can quickly conduct heat to the thermal diffusion layer. The porous matrix in the thermal diffusion layer not only increases the heat dissipation surface area through its porous structure and improves the radiation heat dissipation efficiency, but the filled thermal conductive material further strengthens the heat conduction path, so that the heat can be more evenly dispersed into the surrounding environment. In this way, through the combination and structural design of each layer of material, the synergistic effect of the multi-layer structure is achieved, which not only achieves a firm and stable adhesion between the heat dissipation composite material and the heat-generating electronic devices, but also significantly improves the heat dissipation efficiency and insulation permeability of the heat dissipation composite material, which can meet the heat dissipation needs of high-power density electronic equipment.
[0041] According to some preferred embodiments, the bonding layer is prepared by adding a composite filler and a molecular bridging agent to a polymer matrix material, stirring and mixing, and performing a curing reaction to obtain a bonding layer; the curing includes UV pre-curing and thermal curing; wherein the UV pre-curing time is 30-60s (for example, it can be 30s, 40s, 50s or 60s), the thermal curing temperature is 75-85°C (for example, it can be 75°C, 78°C, 80°C, 82°C or 85°C), and the time is 1-2h (for example, it can be 1h, 1.5h or 2h).
[0042] In the embodiment of the present invention, in the process of preparing the bonding layer, the composite filler is first cleaned with anhydrous ethanol and deionized water respectively, and then placed at a temperature of 60-70°C for vacuum drying for 2-3 hours to remove impurities and moisture on the surface of the filler, thereby ensuring the smooth progress of the subsequent reaction; then the molecular bridging agent is added to the composite filler and stirred at 100-500r / min to fully mix the two, and then the mixed mixture is added to the polymer matrix material and stirred using a high-speed disperser or a planetary mixer, first controlling the stirring rate to 800-1200r / min and stirring for 5-20min. n and then preliminarily mix them evenly, then control the stirring rate to 100-600r / min, continue stirring for 10-40min to ensure uniform dispersion between the various components, transfer the stirred and mixed mixture to a vacuum degassing machine, and degas for 2-20min at a vacuum degree of -0.05MPa to -0.15MPa to remove bubbles introduced during the stirring process and ensure the density and performance stability of the material; finally, during use, the prepared mixture is coated on the surface of the insulating breathable layer and formed into a heat dissipation composite material with other layers, and then the adhesive layer is placed on the surface of the heat-generating electronic device, first at 10mW / cm 2 Pre-curing is carried out under ultraviolet light to form a preliminary bond between the adhesive layer and the surface of the heat-generating electronic device. After that, heat curing is carried out at 80°C for 1 hour to complete the cross-linking reaction, so as to avoid thermal damage to the heat-generating electronic device caused by high-temperature curing.
[0043] According to some preferred embodiments, the composite filler is composed of boron nitride sheets and silver-coated aluminum core-shell particles, the molecular bridging agent is γ-aminopropyltriethoxysilane, γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, bis-[3-(triethoxysilyl)propyl]tetrasulfide or isopropyl tris(dioctyl pyrophosphate) titanate, and the polymer matrix material is polydimethylsiloxane; the boron nitride sheet includes boron nitride nanosheets and Boron nitride microflakes; wherein the particle size of the boron nitride nanoflakes is 50-100 nm (for example, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm), and the particle size of the boron nitride microflakes is 10-20 μm (for example, 10 μm, 12 μm, 15 μm, 18 μm or 20 μm); the mass ratio of the boron nitride nanoflakes to the boron nitride microflakes is (4-8):1 (for example, 4:1, 5:1, 6:1, 7:1 or 8:1).
[0044] In an embodiment of the present invention, polydimethylsiloxane is used as the polymer matrix material, and the active amino group at the end of the polymer molecular chain can enhance the chemical bonding with the surface of the heat-generating electronic device, thereby enhancing the adhesion between the heat-generating electronic device and the heat-dissipating composite material. By further adding a composite filler and a molecular bridging agent, the composite filler is composed of a main filler and a synergistic filler, wherein the main filler is boron nitride flakes, and the synergistic filler is silver-coated aluminum core-shell particles, and the particle size of the silver-coated aluminum core-shell particles is 5-30 μm. Both fillers have good thermal conductivity. Boron nitride sheets provide efficient thermal conductivity within the bonding layer, and silver-coated aluminum core-shell particles can construct a three-dimensional thermal conductive network through inter-particle contact. The two work together to ensure good heat dissipation performance. At the same time, the molecular bridging agent can not only enhance the dispersion of the composite filler in the polymer matrix material, but also the ethoxy group in the molecular bridging agent can condense with the hydroxyl group on the surface of the heat-generating electronic device after hydrolysis, and can react with polydimethylsiloxane to form a chemical bond-physical anchoring dual mechanism. In this way, it can not only ensure that the heat-dissipating composite material and the heat-generating electronic device form a strong and lasting bond, but also effectively reduce the interfacial thermal resistance and promote heat transfer from the heat-generating electronic device to the heat-dissipating composite material.
[0045] Furthermore, the boron nitride flakes in the embodiment of the present invention are preferably obtained by mixing two particle sizes, namely, boron nitride nanoflakes and boron nitride micron flakes. Moreover, by regulating the mass ratio of the boron nitride flakes of the two particle sizes, the nano-sized boron nitride flakes are facilitated to be bonded to the surface of the micron-sized boron nitride flakes, thereby forming a composite granular composite filler similar to a core-shell structure, thereby giving full play to the high thermal conductivity of the composite filler. At the same time, the boron nitride flakes in the embodiment of the present invention are preferably boron nitride flakes that have been subjected to plasma treatment. In this way, hydroxyl groups can be generated on the surface of the boron nitride flakes, thereby forming a hydrogen bond network with the polymer matrix material, further ensuring the stability of the adhesion between the electronic device and the heat dissipation composite material.
[0046] According to some preferred embodiments, the mass percentages of the raw materials in the bonding layer are as follows: 45-70% composite filler (for example, 45%, 50%, 55%, 60%, 65% or 70%), 1-3% molecular bridging agent (1%, 2% or 3%), 27-56% polymer matrix material (for example, 27%, 30%, 42% or 56%), and the mass ratio of boron nitride flakes to silver-coated aluminum core-shell particles is (8-12): (1-2) (for example, 8:1, 8:2, 10:1, 10:2, 12:1 or 12:2).
[0047] In the embodiment of the present invention, by synergistically controlling the proportions of the raw materials in the bonding layer and the mass ratios of the boron nitride sheets and the silver-coated aluminum particles in the composite filler, it is beneficial to ensure that the bonding layer has good bonding performance, thermal conductivity and low interface thermal resistance. Experiments of the present invention have confirmed that if the content of the composite filler is too low, it is not conducive to ensuring good thermal conductivity and high temperature resistance of the bonding layer. If the content of the composite filler is too high, not only will the composite filler agglomerate in the polymer matrix material, but the flexibility of the bonding layer will also be poor. Moreover, if the content of the polymer matrix material is too low, the adhesion of the bonding layer will deteriorate, and the flexibility of the bonding layer will decrease, and cracking will easily occur. If the content of the polymer matrix material is too high, it will not be conducive to ensuring good thermal conductivity of the bonding layer. At the same time, if the content of the molecular bridging agent is too low, it will not be conducive to ensuring the dispersibility of the composite filler. If the content of the molecular bridging agent is too high, the mechanical strength of the bonding layer will be reduced, and the thermal stability of the bonding layer will be adversely affected.
[0048] According to some preferred embodiments, the porous insulating material is expanded polytetrafluoroethylene, expanded polyethylene or expanded polypropylene; the porosity of the porous insulating material is greater than 30%, and the pore size is greater than 0.1 μm.
[0049] In an embodiment of the present invention, the porous insulating material is obtained from expanded polytetrafluoroethylene, expanded polyethylene or expanded polypropylene. The above material has good insulation performance and air permeability, and its surface has a porous structure. In this way, it can allow air circulation while maintaining electrical insulation, effectively preventing heat accumulation, and the microporous structure on its surface can enhance the convective heat dissipation effect, thereby further improving the heat dissipation performance.
[0050] According to some preferred embodiments, the thermal conductivity of the graphene film is 500-5000 W / m·K, and the thickness is 15-20 μm (for example, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm or 20 μm).
[0051] Considering that the graphene film has extremely high thermal conductivity and can quickly conduct heat away, a graphene film of a certain thickness is used as a thermal conductive layer in the embodiment of the present invention. The thermal conductive layer cooperates with other layers to quickly transfer the heat transferred from the heat-generating electronic device to the thermal diffusion layer, and further quickly dissipates the heat into the surrounding environment through the thermal diffusion layer, thereby significantly reducing the residence time of heat inside the heat dissipation composite material and achieving efficient heat conduction.
[0052] It should be noted that the graphene membrane in the embodiment of the present invention is based on graphene as the core material, and is carbonized and graphitized at high temperature through a polymer membrane (such as polyimide, polyetheretherketone, etc.), and then calendered. The specific preparation method can adopt the preparation method in the prior art, and the present invention will not go into details here.
[0053] Continue to refer Figure 1 According to some preferred embodiments, the heat dissipation composite material further includes a thermally conductive transition layer 30 , and the thermally conductive transition layer 30 is located between the insulating breathable layer 20 and the thermally conductive layer 40 .
[0054] According to some preferred embodiments, the thermal conductive transition layer is obtained by compounding graphene nanosheets, carbon nanotubes, silicon carbide nanowires and boron nitride nanosheets; the size of the graphene nanosheets is 5-20 nm (for example, 5 nm, 10 nm, 15 nm or 20 nm), and the content is 40-60% (for example, 40%, 50% or 60%), the size of the boron nitride nanosheets is 5-10 nm (for example, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm), and the content is 5-15% (for example, 40%, 50% or 60%). For example, it can be 5%, 10% or 15%), the size of the carbon nanotubes is 10-50μm (for example, it can be 10μm, 20μm, 30μm, 40μm or 50μm), the content is 20-30% (for example, it can be 20%, 25% or 30%), the diameter of the silicon carbide nanowires is 50-100nm (for example, it can be 50nm, 60nm, 70nm, 80nm, 90nm or 100nm), and the content is 15-25% (for example, it can be 15%, 20% or 25%).
[0055] While the adhesive layer and the insulating and breathable layer can transfer heat from heat-generating electronic devices, their thermal conductivity is relatively weak. The thermally conductive layer, on the other hand, has extremely high thermal conductivity. If the insulating and breathable layer were in direct contact, sudden changes in heat conduction could lead to uneven heat transfer and even thermal stress. Therefore, in embodiments of the present invention, by further providing a thermally conductive transition layer between the insulating and breathable layer and the thermally conductive layer, and by rationally selecting the material and structure of the thermally conductive transition layer, the thermally conductive transition layer can function as a bridge for heat conduction. This allows heat to gradually adapt to the high thermal conductivity environment during transfer from the insulating and breathable layer to the thermally conductive layer, achieving smoother and more uniform heat conduction. Furthermore, considering that the thermally conductive layer is made of graphene film material, which, while having excellent thermal conductivity, is relatively weak in mechanical properties, the thermally conductive transition layer can also provide a certain buffering and protective effect for the thermally conductive layer. The thermally conductive transition layer can disperse some stress and reduce the impact of external mechanical shock on the thermally conductive layer, thereby improving the durability and reliability of the entire heat dissipation material.
[0056] In an embodiment of the present invention, a thermally conductive transition layer is prepared by compositely using graphene nanosheets, carbon nanotubes, silicon carbide nanowires and boron nitride nanosheets of a certain size and content ratio. The appropriate content of graphene nanosheets can significantly enhance the in-plane thermal conductivity, and the addition of a certain content of carbon nanotubes can improve the thermal conductivity in the vertical direction. At the same time, with the addition of an appropriate content of silicon carbide nanowires and boron nitride nanosheets, the mechanical properties and insulation properties can be enhanced. In this way, not only can the thermal conduction path of the thermally conductive transition layer be improved through a multi-dimensional synergistic effect, but the mechanical properties of the thermally conductive transition layer can also be guaranteed, thereby further optimizing the performance of the entire heat dissipation composite material, enabling better matching between the layers during thermal expansion, and reducing the internal stress caused by inconsistent thermal expansion. In addition, the thermally conductive transition layer can achieve a more efficient heat dissipation effect through synergistic action with other layers.
[0057] According to some preferred embodiments, the preparation method of the thermal conductive transition layer is as follows:
[0058] S1, adding graphene nanosheets and boron nitride nanosheets to N-methylpyrrolidone and mixing them by ultrasonication to obtain a first mixed solution;
[0059] S2, adding silicon carbide nanowires and polydimethylsiloxane to the first mixed solution and stirring to obtain a second mixed solution;
[0060] S3, adding carbon nanotubes to the second mixed liquid, stirring and mixing, and applying a vertical magnetic field and gradient temperature curing in sequence to obtain the thermal conductive transition layer.
[0061] In the preparation of the thermal transition layer, polydimethylsiloxane (PDMS) is used as a polymer matrix material and composited with graphene nanosheets, carbon nanotubes, silicon carbide nanowires, and boron nitride nanosheets. PDMS has long, flexible chains that can flexibly wrap around thermally conductive particles such as graphene nanosheets and carbon nanotubes, forming a stable three-dimensional network structure and preventing particle aggregation or sedimentation. Furthermore, PDMS undergoes a cross-linking reaction under heating, solidifying the dispersed thermally conductive particles into a unified thermal transition layer film. This results in a film with low interfacial thermal resistance, a certain degree of toughness, and insulation properties.
[0062] In an embodiment of the present invention, the thermal transition layer is prepared using a three-step mixing method, which allows for full dispersion of the components and ensures uniformity of the materials within the thermal transition layer. After adding carbon nanotubes to the second mixed liquid, a perpendicular magnetic field of a certain strength is applied, causing the carbon nanotubes to align in an orderly manner along the direction of heat flow under the action of the magnetic field. This provides a more efficient channel for heat transfer, thereby improving the thermal conductivity of the thermal transition layer. Furthermore, by controlling the power and duration of the ultrasonic treatment during ultrasonic mixing, as well as the stirring speed and time during stirring, the viscosity of the system can be maintained at 500-1000 cP, thereby ensuring good bonding performance. In an embodiment of the present invention, in step S1, the ultrasonic power is preferably 300-500 W, the duration is 1-2 hours, and the temperature is 25-40°C. In step S2, the stirring speed is preferably 500-800 rpm, the duration is 30-60 minutes, and the temperature is 60-80°C.
[0063] At the same time, in an embodiment of the present invention, graphene nanosheets and silicon carbide nanowires need to be pretreated before preparation. The graphene nanosheets are oxidized by mixing sulfuric acid and nitric acid with a molar ratio of 3:1 to graft carboxyl groups on the surface of the graphene nanosheets. The silicon carbide nanowires are prepared by plasma enhancement, thereby improving the interface bonding strength between the thermal conductive transition layer and other layers.
[0064] According to some preferred embodiments, in the first mixed solution, the mass ratio of the sum of the mass of the graphene nanosheets and the boron nitride nanosheets to the mass of N-methylpyrrolidone is 1:(5-20) (for example, it can be 1:5, 1:10, 1:15 or 1:20); the mass ratio of the silicon carbide nanowires to the polydimethylsiloxane is 1:(1-4) (for example, it can be 1:1, 1:2, 1:3 or 1:4); the intensity of the perpendicular magnetic field is 1-2t (for example, it can be The temperature of each stage in the gradient temperature curing is 70-90°C (for example, 70°C, 80°C or 90°C), 140-160°C (for example, 140°C, 150°C or 160°C), 240-260°C (for example, 240°C, 250°C or 260°C), and the time is 1-2h (for example, 1h, 1.5h or 2h).
[0065] In the embodiments of the present invention, during the preparation of the thermal transition layer, the preparation method and the ratio of the various raw materials are rationally controlled, thereby ensuring not only uniform dispersion of the raw materials but also full synergy between the raw materials, thereby ensuring good thermal conductivity of the thermal transition layer. Furthermore, considering the significant differences in the thermal expansion coefficients of the different raw materials and the matrix, rapid high-temperature curing can easily lead to increased filler movement and agglomeration, and can also cause interfacial stress concentration and microcracks. Therefore, in the embodiments of the present invention, molecular movement and interfacial reactions are controlled in stages through gradient heating, resulting in gradual contraction of the mixed raw materials. This better matches the expansion behavior of the raw materials, reduces internal stress, and realizes the directional construction of a multi-dimensional thermal network, thereby ensuring the thermal conductivity efficiency and mechanical reliability of the thermal transition layer.
[0066] According to some preferred embodiments, the thermal diffusion layer is prepared by the following method: first, thermally conductive nanoparticles (such as copper powder, carbon nanotubes, graphene, silicon carbide or boron nitride) are added to water and ultrasonically mixed (the ultrasonic power and time can be optimized according to the dispersion of the particles, for example, the power is 200-500W and the time is 10-30 minutes) to obtain a nanofiller liquid with a mass concentration of 1-5% (such as 1%, 2%, 3%, 4% or 5%); then, in the process of preparing the porous matrix, the nanofiller liquid is mixed with the raw materials for preparing the porous matrix, and the thermal diffusion layer is obtained after drying or stretching.
[0067] In an embodiment of the present invention, the porous matrix can be selected from one of polyvinylidene fluoride (PVDF), polysulfone (PSU), polyethersulfone (PES), polyacrylonitrile (PAN), polyvinyl chloride (PVC), polyethylene (PE), polypropylene (PP) or polytetrafluoroethylene (PTFE). The preparation method of the porous matrix can be the preparation method of the prior art. For example, PVDF, PSU, PES, PAN, and PVC can induce liquid-liquid phase separation of the polymer solution through solvent / non-solvent exchange to form a porous matrix; PTFE, PE, and PP can be microfibrillated inside the material through unidirectional or bidirectional stretching to form a reticular porous matrix. In the process of forming the thermal diffusion layer, the nanofiller liquid can be mixed with the raw materials for preparing the above-mentioned porous matrix (polymer and solvent / lubricant, etc.) to form a molding. In order to ensure good thermal conductivity of the thermal diffusion layer without affecting the performance of the porous matrix material, in an embodiment of the present invention, the mass of the thermally conductive nanoparticles accounts for 5‰-5% of the mass of the polymer in the porous matrix.
[0068] In an embodiment of the present invention, the porosity of the porous matrix is preferably 60-90%, the average pore size is preferably 0.01-3.00 μm, and the particle size of the thermally conductive nanoparticles is 15-100 nm. When preparing the porous matrix, the thermally conductive nanoparticles are configured as a filling liquid and added to the material for preparing the porous matrix material, thereby trapping the nanoparticles in the filling liquid in the membrane pores of the porous matrix membrane, thereby achieving the filling of the membrane pores by the thermally conductive nanoparticles in the filling liquid. After the filling is completed, the inner cavity of the porous matrix membrane is ultrasonically cleaned for 0.2-1.0 hours and then dried in an oven at 65-75°C for 4.0-8.0 hours to dry, thereby preparing a thermally conductive diffusion layer. During the preparation process of the porous matrix, the porous matrix is filled with the above-mentioned type of thermally conductive particles, thereby forming a composite structure that both conducts heat and expands the heat dissipation area. The porous matrix not only increases the heat dissipation surface area through its porous structure, thereby improving the radiative heat dissipation efficiency, but also the filled thermally conductive material further strengthens the heat conduction path, allowing the heat to be more evenly dispersed to the surrounding environment.
[0069] The present invention also provides a method for preparing any of the above-mentioned heat dissipation composite materials, the preparation method comprising the following steps:
[0070] (1) placing the insulating breathable layer, thermal transition layer, thermal conductive layer and thermal diffusion layer in sequence, and aligning the layers in a laminator;
[0071] (2) controlling the laminating machine to heat to a preset temperature and then pressurize, and maintaining the preset temperature and preset pressure to allow each layer to solidify and bond, and then cool down to form a composite layer;
[0072] (3) Coating an adhesive formed by mixing a composite filler, a molecular bridge agent and a polymer matrix material on the surface of the insulating breathable layer in the composite layer, and obtaining the heat dissipation composite material after curing.
[0073] According to some preferred embodiments, in step (2), the temperature is gradually increased to a preset temperature, the preset temperature is 100-150°C (for example, it can be 100°C, 110°C, 120°C, 130°C, 140°C or 150°C), the preset pressure is 20-30MPa (for example, it can be 20MPa, 25MPa or 30MPa), and the holding time is 30-60min (for example, it can be 30min, 40min, 50min or 60min).
[0074] In an embodiment of the present invention, the prepared layers of materials are placed in sequence and placed in a mold or fixture of a laminator for precise alignment. For example, positioning marks or optical alignment systems can be used to ensure that the relative positions of the layers are accurate and avoid offset or misalignment. Then, considering the different properties of the materials in each layer, the heating temperature of the laminator is controlled by a gradient heating method. First, heating is started at a lower temperature (50-80°C). At this time, the temperature of each layer of material is gradually increased to avoid stress or deformation caused by sudden temperature changes. Then, the temperature is gradually increased to a preset temperature and maintained for 10-30 minutes to achieve better adhesion between the layers of material. At the same time, the laminator is controlled to apply a certain pressure to ensure that the pressure is evenly applied to the entire material combination, eliminate any air that may exist between the layers, and promote physical or chemical bonding between the layers to make the layers fit tightly together. During the pressurization process, the pressure changes should be closely monitored to ensure that the pressure is stable within the specified range, which is conducive to further enhancing the intermolecular forces within the layers of material, forming a stable structure, and making the bonding between the layers of material more firm. After the heat preservation and pressure maintenance are completed, heating is stopped and the temperature is lowered at an appropriate rate (1-5°C / min). At the same time, the pressure is gradually reduced until it is completely released to obtain a composite material. This can avoid the generation of stress within the composite material, which may affect the overall performance of the heat dissipation material. Finally, an adhesive formed by mixing composite fillers, molecular bridge bridging agents, and polymer matrix materials is applied to the surface of the insulating and breathable layer in the composite material. After curing (UV pre-curing and thermal curing), the adhesive layer material and the composite material are fully cured to obtain a heat dissipation composite material.
[0075] In the embodiment of the present invention, the thickness of the bonding layer is preferably 3-50 μm, the thickness of the insulating breathable layer is preferably 30-200 μm, the thickness of the thermal transition layer is preferably 1-30 μm, the thickness of the thermal conductive layer is preferably 15-20 μm, and the thickness of the thermal conductive diffusion layer is preferably 50-300 μm.
[0076] The present invention also provides a use of any of the above-mentioned heat dissipation composite materials in heat dissipation of electronic devices.
[0077] In summary, the heat dissipation composite material prepared in the embodiment of the present invention has a high thermal conductivity, excellent electrical insulation and excellent mechanical properties. The adhesive layer can not only form a firm and lasting bond between the heat dissipation composite material and the surface of the heat-generating electronic device, but also effectively reduce the interfacial thermal resistance and promote the transfer of heat from the heat-generating electronic device to the heat dissipation composite material; the presence of the insulating breathable layer effectively ensures the electrical safety of the electronic equipment, avoids safety hazards such as short circuits, and allows air circulation while maintaining electrical insulation, effectively preventing heat accumulation. At the same time, it further cooperates with the thermal transition layer, the thermal conductive layer and the thermal conductive diffusion layer, so that the heat dissipation composite material has a Z-axis heat conduction path, which can quickly conduct heat energy, avoid heat accumulation, and significantly improve the heat dissipation efficiency. It is suitable for the heat dissipation needs of high power density electronic equipment.
[0078] Furthermore, the heat dissipation composite material is designed with practical application convenience in mind, allowing for easy bonding to heat-generating electronic devices of various shapes. Its preparation is simple and cost-effective. Through optimized material combinations and structural design, the heat dissipation material's mechanical strength and durability are enhanced, making it more adaptable to a variety of complex working environments and application scenarios.
[0079] In order to more clearly illustrate the technical solutions and advantages of the present invention, a heat dissipation composite material, a preparation method thereof, and applications thereof are described in detail through the following embodiments.
[0080] Example 1:
[0081] (1) Preparation of bonding layer: The composite fillers (boron nitride sheets and silver-coated aluminum core-shell particles) were washed twice with anhydrous ethanol, washed once with deionized water, and dried under vacuum at 65°C for 2 h to obtain pretreated boron nitride sheets and silver-coated aluminum core-shell particles; wherein the boron nitride sheets comprised boron nitride nanosheets (particle size 50-100 nm) and boron nitride microsheets (particle size 10-20 μm) in a mass ratio of 5:1, and the boron nitride sheets were plasma-treated boron nitride sheets;
[0082] A molecular bridging agent (γ-aminopropyltriethoxysilane) was added to the pretreated composite filler (boron nitride sheets and silver-coated aluminum core-shell particles (mass ratio of 10:1)) and stirred at 200 r / min for 10 minutes to obtain a mixed solution; the mixed solution was added to a polymer matrix material (polydimethylsiloxane) and placed in a high-speed disperser and stirred at 1000 r / min for 10 minutes, then reduced to 500 r / min and stirred for 30 minutes; thereafter, it was transferred to a vacuum deaerator and degassed at -0.10 MPa for 5 minutes to obtain a bonding layer precursor; wherein the content of the composite filler was 50wt%, the content of the molecular bridging agent was 2%, and the content of the polymer matrix material was 48%;
[0083] Preparation of thermal conductive transition layer:
[0084] S1. Oxidize the graphene nanosheets with a mixture of sulfuric acid and nitric acid at a molar ratio of 3:1, and treat the silicon carbide nanowires with plasma (power 500W, treatment time 10min) to obtain pretreated graphene nanosheets and silicon carbide nanofibers; add the graphene nanosheets and boron nitride nanosheets to N-methylpyrrolidone at 30°C and ultrasonically mix for 2h (power 400W, ultrasonic frequency 40kHz) to ensure uniform dispersion. Obtain a first mixed solution; wherein, in the first mixed solution, the proportion of N-methylpyrrolidone (NMP) is 10%, the content of boron nitride nanosheets (thickness less than 10nm) is 15%, and the content of graphene nanosheets (lateral size 5-20μm) is 55%;
[0085] S2. Raising the temperature to 60° C., adding silicon carbide nanowires and polydimethylsiloxane to the first mixed solution and stirring at 600 rpm for 1 hour to obtain a second mixed solution; the total proportion of silicon carbide nanowires and polydimethylsiloxane in the second mixed solution is 50%, wherein the mass ratio of silicon carbide nanowires to polydimethylsiloxane is 1:4 (i.e., 10% silicon carbide nanowires and 40% polydimethylsiloxane);
[0086] S3. Add 10 g of carbon nanotubes to the second mixed solution and stir to mix. Then, apply a 1 T vertical magnetic field in sequence. Then, heat the mixed system in a gradient from 80°C to 150°C to 250°C for curing. Each temperature is maintained for 1 hour to obtain a thermally conductive transition layer.
[0087] Preparation of the thermal diffusion layer: Thermally conductive nanoparticles (copper powder) were added to water and ultrasonically mixed to obtain a nanofiller with a mass concentration of 5%. Polytetrafluoroethylene (PTFE, Shandong Dongyue brand D204) powder, lubricant (Isopar M from Mobil Corporation), and the nanofiller were mixed in a mass ratio of 100:25:20. After thorough mixing, the mixture was dried (at 60°C for 4 hours) and pressed into a blank. The blank was extruded through a plunger to form a film, which was then longitudinally stretched (at a rate of 600% / s and a temperature of 320°C) to form a microfiber network. The film was then transversely stretched (at a rate of 1000% / s and a temperature of 310°C) to form a spider web-like structure. This uniformly distributed the thermally conductive nanoparticles within the porous PTFE (expanded polytetrafluoroethylene) film, forming the thermal diffusion layer. The thermally conductive nanoparticles accounted for 1% of the mass of the polytetrafluoroethylene in the porous matrix.
[0088] Place the insulating breathable layer (expanded polytetrafluoroethylene), the thermally conductive transition layer prepared above, the thermally conductive layer (graphene film), and the thermally conductive diffusion layer prepared above in sequence, and align the layers in a laminator, using positioning marks to ensure the relative positions of the layers are accurate;
[0089] (2) Control the laminator to heat to a preset temperature and then pressurize. Set the heating temperature of the laminator, start heating at a lower temperature of 50°C, then gradually increase the temperature to a preset temperature of 100°C and maintain it for 10 minutes. At the same time, start applying a preset pressure of 20 MPa and maintain it at this temperature and pressure for 30 minutes. Then, reduce the temperature at a rate of 3°C / min and gradually reduce the pressure until it is completely released to obtain a composite layer.
[0090] (3) Place the adhesive layer on the upper surface of the insulating and breathable layer in the composite layer and bond it to the surface of the heat-generating electronic device. 2 The heat dissipation composite material is obtained by pre-curing the adhesive layer under ultraviolet light for 30 seconds to form a preliminary bond between the adhesive layer and the surface of the heat-generating electronic device, and then heat-curing the adhesive layer at 80° C. for 1 hour to complete the cross-linking reaction.
[0091] Example 2:
[0092] (1) Preparation of bonding layer: The composite fillers (boron nitride sheets and silver-coated aluminum core-shell particles) were washed twice with anhydrous ethanol, washed once with deionized water, and dried under vacuum at 65°C for 2 h to obtain pretreated boron nitride sheets and silver-coated aluminum core-shell particles; wherein the boron nitride sheets comprised boron nitride nanosheets (particle size 50-100 nm) and boron nitride microsheets (particle size 10-20 μm) in a mass ratio of 8:1, and the boron nitride sheets were plasma-treated boron nitride sheets;
[0093] A molecular bridging agent (γ-aminopropyltriethoxysilane) was added to the pretreated composite filler (boron nitride sheets and silver-coated aluminum core-shell particles (mass ratio of 8:1)) and stirred at 200 r / min for 10 minutes to obtain a mixed solution; the mixed solution was added to a polymer matrix material (polydimethylsiloxane) and placed in a high-speed disperser and stirred at 1000 r / min for 10 minutes, then reduced to 500 r / min and stirred for 30 minutes; thereafter, it was transferred to a vacuum deaerator and degassed at -0.10 MPa for 5 minutes to obtain a bonding layer precursor; wherein the content of the composite filler was 70wt%, the content of the molecular bridging agent was 3%, and the content of the polymer matrix material was 27%;
[0094] Preparation of thermal conductive transition layer:
[0095] S1. Oxidizing graphene nanosheets with a mixture of sulfuric acid and nitric acid in a molar ratio of 3:1, and treating silicon carbide nanowires with plasma to obtain pretreated graphene nanosheets and silicon carbide nanofibers; adding the pretreated graphene nanosheets and boron nitride nanosheets to N-methylpyrrolidone at 30° C. and ultrasonically mixing for 2 hours to obtain a first mixed solution; wherein, in the first mixed solution, the content of N-methylpyrrolidone is 10%, the content of boron nitride nanosheets (thickness less than 10 nm) is 15%, and the content of graphene nanosheets (lateral size 5-20 μm) is 55%;
[0096] S2. Raising the temperature to 60° C., adding silicon carbide nanowires and polydimethylsiloxane to the first mixed solution and stirring at 2000 rpm for 1 hour to obtain a second mixed solution; wherein the mass ratio of silicon carbide nanowires to polydimethylsiloxane is 1:4 (i.e., silicon carbide nanowires account for 10% of the second mixed solution and polydimethylsiloxane accounts for 40%), and the mixing ratio of the first mixed solution to the second mixed solution is 50:50 (mass ratio);
[0097] S3. Add 10 g of carbon nanotubes to the second mixed solution and stir to mix. Then, apply a 1 T vertical magnetic field in sequence. Then, heat the mixed system in a gradient from 80°C to 150°C to 250°C for curing. Each temperature is maintained for 1 hour to obtain a thermally conductive transition layer.
[0098] Preparation of the thermal diffusion layer: Thermally conductive nanoparticles (copper powder) were added to water and ultrasonically mixed to obtain a nanofiller with a mass concentration of 3%. Polytetrafluoroethylene (PTFE, Shandong Dongyue brand D204) powder, lubricant (Isopar M from Mobil Corporation), and the nanofiller were mixed in a mass ratio of 100:25:10. After thorough mixing, the mixture was dried (at 60°C for 4 hours) and pressed into a billet. The billet was extruded through a plunger to form a film, which was then longitudinally stretched (at a rate of 600% / s and a temperature of 320°C) to form a microfiber network. The film was then transversely stretched (at a rate of 1000% / s and a temperature of 310°C) to form a spider web-like structure, thereby uniformly distributing the thermally conductive nanoparticles throughout the porous PTFE (expanded polytetrafluoroethylene) film to form the thermal diffusion layer. The mass of the thermally conductive nanoparticles accounted for 0.3% of the mass of the polytetrafluoroethylene in the porous matrix.
[0099] Place the insulating breathable layer (expanded polytetrafluoroethylene), the thermally conductive transition layer prepared above, the thermally conductive layer (graphene film), and the thermally conductive diffusion layer prepared above in sequence, and align the layers in a laminator, using positioning marks to ensure the relative positions of the layers are accurate;
[0100] (2) Start heating at a lower temperature of 60°C, control the laminator to heat to the preset temperature and then pressurize, then gradually increase the temperature to the preset temperature of 120°C and maintain it for 10 minutes. At the same time, start applying a preset pressure of 25 MPa and maintain it at this temperature and pressure for 30 minutes. Then, reduce the temperature at a rate of 3°C / min and gradually reduce the pressure until it is completely released to obtain a composite layer.
[0101] (3) Place the adhesive layer on the upper surface of the insulating and breathable layer in the composite layer and bond it to the surface of the heat-generating electronic device. 2 The heat dissipation composite material is obtained by pre-curing the adhesive layer under ultraviolet light for 60 seconds to form a preliminary bond between the adhesive layer and the surface of the heat-generating electronic device, and then heat-curing the adhesive layer at 75° C. for 2 hours to complete the cross-linking reaction.
[0102] Example 3:
[0103] Example 3 is basically the same as Example 1, except that: in step (1), during the bonding layer preparation process, the boron nitride sheets in the composite filler are only boron nitride nanosheets.
[0104] Example 4:
[0105] Example 4 is basically the same as Example 1, except that: in step (1), during the bonding layer preparation process, the mass ratio of boron nitride sheets to silver-coated aluminum core-shell particles in the composite filler is 15:1.
[0106] Example 5:
[0107] Example 5 is basically the same as Example 1, except that: in step (1), during the preparation of the bonding layer, the content of the polymer matrix material is 65%, the content of the composite filler is 37%, and the content of the molecular bridging agent is 3%.
[0108] Example 6
[0109] Example 6 is basically the same as Example 1, except that: in step (1), during the preparation of the thermal conductive transition layer, the content of graphene nanosheets is 70%, the content of boron nitride nanosheets is 5%, the content of carbon nanotubes is 10%, and the content of silicon carbide nanowires is 5%.
[0110] Example 7
[0111] Example 7 is basically the same as Example 1, except that: in step (1), during the preparation of the thermal conductive transition layer, the content of graphene nanosheets is 40%, the content of boron nitride nanosheets is 20%, the content of carbon nanotubes is 15%, and the content of silicon carbide nanowires is 25%.
[0112] Example 8
[0113] Example 8 is basically the same as Example 1, except that: in step (1), in step S3 of the thermal transition layer preparation process, the mixed system is directly heated to 250°C and the temperature is maintained for 1 hour to obtain the thermal transition layer.
[0114] Example 9
[0115] Example 9 is basically the same as Example 1, except that in step (1), no thermally conductive transition layer is provided between the insulating breathable layer and the thermally conductive layer.
[0116] Comparative Example 1
[0117] Comparative Example 1 is substantially the same as Example 1, except that in step (1), the adhesive layer is replaced by a silicone layer of the same thickness.
[0118] Comparative Example 2
[0119] Comparative Example 2 is substantially the same as Example 1, except that in step (1), during the preparation of the bonding layer, the composite filler only includes boron nitride sheets.
[0120] Comparative Example 3
[0121] Comparative Example 3 is substantially the same as Example 1, except that in step (1), the thermal diffusion layer is a porous polytetrafluoroethylene membrane.
[0122] Comparative Example 4
[0123] Comparative Example 4 is substantially the same as Example 1, except that in step (1), no heat-conducting diffusion layer is included.
[0124] The heat dissipation composite materials in Examples 1 to 9 and Comparative Examples 1 to 4 were subjected to performance tests, and the test results are shown in Table 1.
[0125] Adhesion performance (peel strength) test: in accordance with GB / T2792-2014_Test method for peel strength of adhesive tape;
[0126] Thermal conductivity test: in accordance with GB / T 10294-2008 Insulation materials - Determination of steady-state thermal resistance and related properties - guarded hot plate method;
[0127] Resistivity test: Using the four-probe method, the resistivity is calculated by measuring the voltage difference and current value between the four probes according to Ohm's law (V = IRV = IRV = IR):
[0128] Mechanical properties test: in accordance with GB / T 1447-2005: Test method for tensile properties of fiber reinforced plastics.
[0129] Table 1
[0130]
[0131]
[0132] As can be seen from Table 1, the heat dissipation composite material prepared in the embodiment of the present invention has excellent heat dissipation efficiency and insulation performance through the mutual cooperation between the layers. It is suitable for the heat dissipation needs of high-power density electronic equipment and can be stably adhered to the surfaces of heat-generating electronic devices of various shapes.
[0133] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the various embodiments of the present invention.
Claims
1. A heat dissipation composite material, characterized in that: It includes an adhesive layer, an insulating and breathable layer, a thermally conductive layer and a thermally conductive diffusion layer arranged in sequence from bottom to top; wherein, the adhesive layer is obtained by a mixed reaction of a polymer matrix material, a composite filler and a molecular bridging agent, the insulating and breathable layer is a porous insulating material, the thermally conductive layer is a graphene film, and the thermally conductive diffusion layer is prepared from porous matrix composite thermally conductive nanoparticles.
2. The heat dissipation composite material according to claim 1, characterized in that: The bonding layer is prepared by adding the composite filler and the molecular bridging agent into the polymer matrix material, stirring and mixing, and performing a curing reaction to obtain the bonding layer; Preferably, the curing includes UV pre-curing and thermal curing; wherein, the UV pre-curing time is 30-60s, and the thermal curing temperature is 75-85°C and the time is 1-2h.
3. The heat dissipation composite material according to claim 1 or 2, characterized in that: The composite filler is composed of boron nitride sheets and silver-coated aluminum core-shell particles, the molecular bridging agent is γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, bis-[3-(triethoxysilyl)propyl]tetrasulfide or isopropyl tris(dioctylpyrophosphate) titanate, and the polymer matrix material is polydimethylsiloxane; Preferably, the boron nitride sheets include boron nitride nanosheets and boron nitride microsheets; wherein the particle size of the boron nitride nanosheets is 50-100 nm, and the particle size of the boron nitride microsheets is 10-20 μm; More preferably, the mass ratio of the boron nitride nanosheets to the boron nitride microsheets is (4-8):1; and / or The mass percentages of the raw materials in the bonding layer are as follows: 45-70% of composite filler, 1-3% of molecular bridging agent, 27-56% of polymer matrix material, and the mass ratio of boron nitride sheets and silver-coated aluminum core-shell particles is (8-12):(1-2).
4. The heat dissipation composite material according to claim 1, characterized in that: The porous insulating material is expanded polytetrafluoroethylene, expanded polyethylene or expanded polypropylene; Preferably, the porous insulating material has a porosity greater than 30% and a pore size greater than 0.1 μm; and / or The thermal conductivity of the graphene film is 500-5000 W / m·K, and the thickness is 15-20 μm.
5. The heat dissipation composite material according to claim 1, characterized in that: The heat dissipation composite material further comprises a heat conductive transition layer, wherein the heat conductive transition layer is located between the insulating breathable layer and the heat conductive layer; Preferably, the thermal conductive transition layer is obtained by compounding graphene nanosheets, carbon nanotubes, silicon carbide nanowires and boron nitride nanosheets; More preferably, the size of graphene nanosheets is 5-20 nm, the content is 40-60%, the size of boron nitride nanosheets is 5-10 nm, the content is 5-15%, the size of carbon nanotubes is 10-50 μm, the content is 20-30%, and the diameter of silicon carbide nanowires is 50-100 nm, the content is 15-25%.
6. The heat dissipation composite material according to claim 5, characterized in that: The preparation method of the thermal conductive transition layer is as follows: S1, adding graphene nanosheets and boron nitride nanosheets to N-methylpyrrolidone and mixing them by ultrasonication to obtain a first mixed solution; S2, adding silicon carbide nanowires and polydimethylsiloxane to the first mixed solution and stirring to obtain a second mixed solution; S3, adding carbon nanotubes to the second mixed liquid, stirring and mixing, and applying a vertical magnetic field and gradient temperature curing in sequence to obtain the thermal conductive transition layer; Preferably, in the first mixed solution, the ratio of the sum of the mass of the graphene nanosheets and the boron nitride nanosheets to the mass of N-methylpyrrolidone is 1:(5-20); More preferably, the mass ratio of silicon carbide nanowires to polydimethylsiloxane is 1:(1-4); and / or The intensity of the vertical magnetic field is 1-2t, and the temperature of each stage in the gradient temperature rise curing is 70-90° C., 140-160° C., and 240-260° C. in sequence, and the time is 1-2 hours.
7. The heat dissipation composite material according to claim 1, characterized in that: The porous matrix is polyvinylidene fluoride, polysulfone, polyethersulfone, polyacrylonitrile, polyvinyl chloride, polypropylene or polytetrafluoroethylene; Preferably, the thermally conductive nanoparticles are copper powder, carbon nanotubes, graphene, silicon carbide or boron nitride.
8. The method for preparing the heat dissipation composite material according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) placing the insulating breathable layer, thermal transition layer, thermal conductive layer and thermal diffusion layer in sequence, and aligning the layers in a laminator; (2) controlling the laminator to heat to a preset temperature and then pressurize, and maintaining the preset temperature and preset pressure to allow each layer to solidify and bond, and obtaining a composite layer after cooling; (3) Coating an adhesive formed by mixing a composite filler, a molecular bridge agent and a polymer matrix material on the surface of the insulating breathable layer in the composite layer, and obtaining the heat dissipation composite material after curing.
9. The preparation method according to claim 8, characterized in that In step (2), the temperature is increased to a preset temperature by gradient, the preset temperature is 100-150° C., the preset pressure is 20-30 MPa, and the holding time is 30-60 min.
10. Use of the heat dissipation composite material according to any one of claims 1 to 7 in heat dissipation of electronic devices.
Citation Information
Cited By
Self-adaptive heat dissipation electronic heat management composite material as well as preparation method and application thereof
CN122213479A
Identification of clays in porous media by integrating electromagnetic measurements and temperature gradient analysis
US20250155397A1